The Dark Matter Annihilation Signal from Dwarf Galaxies and Subhalos - Michael Kuhlen (Advances in Astronomy, 2010)
Dark Matter annihilation holds great potential for directly probing the clumpiness of the Galactic halo that is one of the key predictions of the Cold Dark Matter paradigm of hierarchical structure formation. Here we review the 𝛾-ray signal arising from dark matter annihilation in the centers of Galactic subhalos. We consider both known Galactic dwarf satellite galaxies and dark clumps without a stellar component as potential sources. Utilizing the Via Lactea II numerical simulation, we estimate fluxes for 18 Galactic dwarf spheroidals with published central densities. The most promising source is Segue 1, followed by Ursa Major II, Ursa Minor, Draco, and Carina. We show that if any of the known Galactic satellites can be detected, then at least ten times more subhalos should be visible, with a significant fraction of them being dark clumps.